Basic Humor Techniques of Arthur A. Berger - Vesna Trifunović (University of Belgrade, 2016)
The essay deals with basic techniques that can be detected in various humor genres, whose rationale is to generate amusement. A long list of basic humor techniques has come to attention as a result of problematising and analysis of different humor genres done by the American media professor Arthur A. Berger. A. Berger is by and large unknown to the Serbian scientific community, so the initial piece of the thesis is dedicated to the presentation of the aforementioned author and his body of work. What follows are the basic humor techniques that are perused through native yarns. Berger believes that the joke, due to its condensed form, is a particularly successful vehicle for illuminating the functioning of humor techniques, an explanation that is an integral part of the thesis. It is evident that not all techniques are helpful in the examination of jokes, which is why it was necessary, for a number of them, to divulge other humor genres. This fact, as indeed many others, has led to a critical reexamination of Berger's techniques and to analysis of how they could be further developed, modified and used in anthropological and folklore researcher, a matter that is dealt with in the conclusion. Basic humor techniques that are identified by Arthur A. Berger as containing great methodological potency that can be of significance in the analysis of different genres and narratives. As such, these techniques are certainly an admirable form from the standpoint of the effort that was put into their formation.